2009
DOI: 10.1007/s00436-009-1402-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological differences and molecular similarities between Paragonimus bangkokensis and P. harinasutai

Abstract: Paragonimus bangkokensis and Paragonimus harinasutai were found one after another in the same crab host, Potamon smithianus, in Thailand in 1967 and 1968. Both species were also recently found in China and Lao People's Democratic Republic (PDR). Those two Paragonimus spp. are distinguishable from each other by morphological features of metacercariae and adults. However, recently, the DNA sequences of second internal transcribed spacer region (ITS2) and cytochrome oxidase subunit 1 (CO1) genes of those two spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In the present study, molecular phylogenetic analyses revealed that P. paishuihoensis isolates from Lao PDR and Thailand were genetically almost completely identical with each other, thus forming a moderately to well-supported group in ITS2 and CO1 trees. Consistent with the previous reports [14,15], P. paishuihoensis sequences were clustered with P. harinasutai of China with a moderate bootstrap value of 76% to make a group separated from the rest of the P. bangkokensis / P. harinasutai . However, grouping with P. paishuihoensis and P. bangkokensis / P. harinasutai complex was supported by very low bootstrap values (less than 50%), especially in CO1 tree.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, molecular phylogenetic analyses revealed that P. paishuihoensis isolates from Lao PDR and Thailand were genetically almost completely identical with each other, thus forming a moderately to well-supported group in ITS2 and CO1 trees. Consistent with the previous reports [14,15], P. paishuihoensis sequences were clustered with P. harinasutai of China with a moderate bootstrap value of 76% to make a group separated from the rest of the P. bangkokensis / P. harinasutai . However, grouping with P. paishuihoensis and P. bangkokensis / P. harinasutai complex was supported by very low bootstrap values (less than 50%), especially in CO1 tree.…”
Section: Discussionsupporting
confidence: 90%
“…1) in addition to 3 previously reported species; P. harinasutai , Paragonimus heterotremus , and P. bangkokensis [13,14]. By light microscopic observations, these metacercariae were spherical in shape with 2 cyst walls (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…Two types of indels (AT and ATC) were independently observed in ITS2 sequences among P. harinasutai / P. bangkokensis populations. These indels are not species-specific, but have some tendencies to associate with particular geographical populations, indicating recent gene flow between P. harinasutai and P. bangkokensis and recent divergence of these 2 species [16,18]. The recent discovery of naturally hybridized specimen between P. bangkokensis and P. harinasutai in central Vietnam [35] strongly supports their close relationship in the same species complex.…”
Section: Inter- and Intra-species Variation And Molecular Phylogenetimentioning
confidence: 97%
“…In that study, P. ohirai was identified based on the presence of grouped spines on the worm surface and possession of a ventral sucker that was larger than the oral sucker. However, these characters are also seen in other species, P. bangkokensis and P. proliferus , of which metacercariae were also discovered in Sin Ho district, Lai Chau Province [15,16]. Metacercariae of P. ohirai have never been found in freshwater crabs in Vietnam.…”
Section: Geographical Distributionmentioning
confidence: 99%
See 1 more Smart Citation